Analisis Pengaruh Pengetahuan, Persepsi, dan Isyarat untuk Bertindak terhadap Penerimaan Pelaksanaan Pemeriksaan Mantoux Test pada Ibu yang Mempunyai Balita Terduga TBC - Birroudhoh, Fiqhiyah; Prasetyo, Joko; Peristiowati, Yuly (Journal of Telenursing (JOTING), 2025)
This study aims to determine the influence of knowledge, perception, and cues to action on the acceptance of the implementation of the Mantoux test in mothers who have toddlers suspected of having TB at the Rengel Community Health Center, Tuban Regency. This research method is quantitative with a cross-sectional approach. The results of this study found that knowledge was good (88.2%), perception of moderate susceptibility (79.1%), perception of mild severity (68.2%), perception of moderate benefits (73.6%), perception of moderate barriers (84.5%), and cues to action were moderate (74.5%). The results of the partial regression analysis of each independent variable were: there was no influence of the knowledge factor (α = 0.542), perception of susceptibility (α = 0.124), perception of severity (α = 0.969), perception of benefits (α = 0.661), and there was an influence of the perception of barriers (α = 0.000) and the cues to action factor (α = 0.000) on the acceptance of the Mantoux test. The analysis simultaneously showed that knowledge, perceptions (susceptibility, severity, benefits, barriers), and cues to action influenced acceptance of the Mantoux test, with a significance value of α = 0.000 (<α = 0.05). Acceptance of the Mantoux test was influenced by knowledge, perceptions, and cues to action by 86.9% (Adjusted R Square: 0.869), with perceived barriers (β = 0.969) having a greater influence than cues to action (β = 0.626). In conclusion, providing detailed information about childhood TB, susceptibility and severity, benefits, early detection, and the importance of the Mantoux test is necessary. This necessitates effective collaboration between health workers, cadres, and related parties.   Keywords: Mantoux test, Acceptance, HBM Theory